Left sided Superior Vena cava: (A case report and review of literature) - Sharma, Om Prakash; Shanmugam, Senthil (Asian Journal of Medical Sciences, 2010)
A male child aged about one and half year old was referred to the department of Radio diagnosis for CT vena cavography after he was examined on 2 Dimensional echocardiography which revealed the diagnosis of Fallot's tetralogy. On CT scan besides the confirmation of presence of Tetralogy, there was an abnormal finding of left sided superior vena cava, an uncommon association. A male child aged about one and half year old was referred to the department of Radio diagnosis for CT vena cavography after he was examined on 2- dimensional echocardiography which revealed the diagnosis of Fallot's tetralogy. On CT scan besides the confirmation of presence of Tetralogy, there was an abnormal finding of left sided superior vena cava, an uncommon association. Keywords: Persistent left superior vena cava; 64 slice CT; developmental malformation DOI: 10.3126/ajms.v1i1.2508 Asian Journal of Medical Sciences Vol.1(1) 2010 p.18-19